(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: This study suggest that trans cerebellar diameter is not only a good parameter for estimating gestational age in normal but also in estimation during IUGR pregnancies. Objective: To compare and evaluate the accuracy of TCD based gestational age in estimating gestational age with other fetal biometrics in IUGR and non-IUGR patients in second and third trimesters. Methods: A cross-sectional study conducted at Hawwa Hospital, Wazirabad, Pakistan for four months from 01 June 2024 to 30 September 2024, including 270 pregnant women in their second or third trimesters. Used a convenient sampling technique and collected data using fetal biometric including Trans-cerebellar Diameter, femur length, biparietal diameter, abdominal circumference, head circumference, OFD and LMP. Statistical analyses were done to determine the associations between parameters of IUGR and non-IUGR pregnancies. Results: TCD showed highest GA estimation in IUGR cases. Paired t-tests evaluated that GA estimated by TCD showed a large difference for AC (+2.16 weeks) and FL (+2.01 weeks) (p < 0.001) in IUGR pregnancies. Pearson’s correlation demonstrated a high association between other GA estimation methods and TCD in both groups, having correlations with LMP (r = 0.979) and AC (r = 0.879) in IUGR. These findings justify the reliability of TCD for GA estimation in IUGR subjects, where traditional biometrics appear to be less accurate. Conclusion: TCD displayed a significant correlation with fetal biometrics for estimating gestational age. Its relationship with LMP and resistance to growth disturbances provides valuable insight for obstetric care and reduces the perinatal morbidity and mortality risk.